2009
DOI: 10.1021/ja903149u
|View full text |Cite
|
Sign up to set email alerts
|

Marinopyrrole A Target Elucidation by Acyl Dye Transfer

Abstract: The targeting of marinopyrrole A to actin was identified using a fluorescent dye transfer strategy. The process began by appending a carboxylic acid terminal tag to a phenol in the natural product. The resulting probe was then studied in live cells to verify that it maintained activity comparable to marinopyrrole A. Two-color fluorescence microscopy confirmed that both unlabeled and labeled materials share comparable uptake and subcellular localization in HCT-116 cells. Subsequent immunoprecipitation studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 33 publications
(26 reference statements)
1
87
0
3
Order By: Relevance
“…mode of action | chemical biology | drug discovery | marine natural products | cancer O ver the last decade, we have found that integrating a streamlined transition between marine natural products discovery (1), detailed cell and molecular biological studies (2), and medicinal chemical optimization offers a rich forum to advance leads that escape industrialized high-throughput practices (3)(4)(5). One place where drug discovery continues to be challenged lies in the discovery of new agents, which are highly selective for specific cancers (6)(7)(8).…”
mentioning
confidence: 99%
“…mode of action | chemical biology | drug discovery | marine natural products | cancer O ver the last decade, we have found that integrating a streamlined transition between marine natural products discovery (1), detailed cell and molecular biological studies (2), and medicinal chemical optimization offers a rich forum to advance leads that escape industrialized high-throughput practices (3)(4)(5). One place where drug discovery continues to be challenged lies in the discovery of new agents, which are highly selective for specific cancers (6)(7)(8).…”
mentioning
confidence: 99%
“…10,11 The second case study explores an extension of the IAF approach to monitor protein natural product interactions through the transfer of an IAF tag from the natural product to its protein target upon binding. 12 In this study, we demonstrate how this 'tag-transfer' concept works through studies on the marinopyrrole natural products. 13,14 The final two case studies on the seriniquinone 15 and chlorizidine 16,17 natural products define how further extension into downstream and cell cycle markers allows one to develop a streamlined connectivity between cellular processing, its associated molecular targets, and ultimate downstream effects.…”
Section: Resultsmentioning
confidence: 87%
“…With structures at hand, we then turned our effort to explore their target identification and associated MOA in HCT-116 cells. 12 While only moderately cytotoxic, we were interested in exploring if these materials targeted pathways that may not be directly related with cell death phenotypes.…”
Section: Case Study 2: the Marinopyrroles Target Actinmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel labeling experiments against the target protein carbonic anhydrase have shown that the moderately reactive epoxide crosslinker exhibits the optimal balance of selectivity and reactivity (Chen et al 2003). Hamachi, Fenical and their respective co-workers developed a series of novel traceless affinity labeling probes containing electrophilic organocatalysts such as acyl phenolate, (Hughes et al 2009) 4-dimethylaminopyridine (DMAP) (Koshi et al 2008;Sun et al 2011;Wang et al 2011), tosylate, (Tsukiji et al 2009a, b;Tamura et al 2012), and acyl imidazole (Fujishima et al 2012;Matsuo et al 2013;Miki et al 2014). By targeting specific nucleophilic groups in the ligand-binding pocket of the protein, these probes exhibited high target specificity (Fig.…”
Section: Covalent Crosslinkingmentioning
confidence: 99%